Agronomic Characteristics and Harvest Time as Determinants of Starch Production in Smallholder Sago Palm Plantations - Suswanto, Iman; Maherawati; Sunarti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2023)
Smallholder sago plantations generally use simple technology, resulting in the determination of harvest time based solely on the physical appearance of plants. This study aims to identify the agronomic characteristics of sago that influence starch yield. The research was conducted on smallholder sago plantations, and samples of sago plants were collected at four harvest phases based on local customs: Dewasa, Jantung, Rusa, and Bunga. Observations on agronomic characteristics included the number of suckers, plant height, pith diameter, number of leaves, number of leaf scars, number of leaflets, leaflet length, and leaflet width. ANOVA and multiple comparisons were utilized to identify differences between treatments in starch yield. Regression analysis was employed to establish the relationship between starch yield and agronomic characteristics, while path analysis determined the direct/indirect effects of agronomic characteristics on starch yield. The results indicated that the optimal harvest time is during the Jantung and Rusa phases. The agronomic components that significantly influence sago starch yield are pith diameter and leaf scars. According to the coefficient of determination value, the production model can be expressed as Y = -63.26 + 2.44x1 (R2=37%). To enhance starch yield, it is crucial to improve plant spacing. When the plant spacing is too close, with a population density exceeding 200 clumps/ha, overlapping leaves occur, negatively impacting sago starch formation. This negative effect intensifies with an increase in the number of leaves and the size of leaflets in terms of length and width. Keywords: sago plantations, agronomic characteristics, harvest time determination, starch yield, smallholder agriculture